Columnar propeller-like 1, 3, 5-triphenylbenzenes: the missing link of shape-persistent hekates. Issue 16 (16th March 2016) - Wöhrle, Tobias; Beardsworth, Stuart James; Schilling, Christopher; Baro, Angelika; Giesselmann, Frank; Laschat, Sabine
Abstract : Triphenylbenzenes with nine peripheral n -alkoxy side chains form enantiotropic, highly ordered columnar hexagonal mesophases near room temperature. Wide-angle X-ray data indicate a helical stacking in columns. Abstract : Triphenylbenzenes with different substitution patterns at the outer phenyl rings have been successfully synthesised. Sixfold n -alkoxy substitution was insufficient for mesomorphism, but already increasing the number of side chains by three methoxy groups led to liquid crystalline behaviour and mesophase formation. Symmetrical triphenylbenzenes with nine n -alkoxy side chains (≥C9) formed broad enantiotropic mesophases. The symmetry of the liquid crystalline phases was unambiguously determined by X-ray diffraction measurements as Colh and Colho for symmetry-reduced methoxy–alkoxy derivatives and symmetrical nona-alkoxy-triphenylbenzenes, respectively. Based on X-ray diffraction data a stacking model was proposed in which the single molecules aggregate to helical columns forming a mesophase.